To rewrite the expression \(7^{-3} \cdot 7^{-5}\) with positive exponents only, you can use the property of exponents that states:
\[ a^m \cdot a^n = a^{m+n} \]
Applying that property here:
\[ 7^{-3} \cdot 7^{-5} = 7^{-3 + (-5)} = 7^{-8} \]
Now, to convert \(7^{-8}\) into an expression with positive exponents, you use the property that states:
\[ a^{-n} = \frac{1}{a^n} \]
So,
\[ 7^{-8} = \frac{1}{7^8} \]
Thus, the expression \(7^{-3} \cdot 7^{-5}\) with positive exponents only is:
\[ \frac{1}{7^8} \]